The timing of repeated and unrepeated monopoly investment under wear and tear and demand growth - Jörg Borrmann; Gert Brunekreeft (Jacobs University Bremen, Bremer Energie Institut, 2011)
In an intertemporal model, we analyze the timing of irreversible and lumpy monopoly investment under certainty. There are two reasons for investing, i.e. wear and tear leading to replacement investment and demand growth leading to expansion investment. Both in a single investment setting and in a repeated investment setting, we find that a firm maximizing discounted social welfare invests earlier than an identical firm maximizing discounted profits. The investment date of an identical firm maximizing a discounted convex combination of social welfare and profits lies between these polar cases. All results apply both to replacement investment and to expansion investment.
Keywords: D42; G00; L20; 330; Expansion investment; Investment timing; Monopoly; Repeated investment; Replacement investment